Correlation between Maltese and euro area sovereign bond yields - Reuben Ellul (Central Bank of Malta, 2017)
This paper investigates correlation in Malta government stock (MGS) yields and assesses correlation between these yields and those of Malta's major euro area partners. Correlation coefficients are found to be high, indicating the existence of a long-run relationship in the setting of MGS yields with short-term deviations. The analysis also includes an MGARCH-DCC(1,1) system based on spreads over the German ten-year bond, which are modelled for eleven euro area countries. Dynamic conditional correlations (DCCs) confirm that Maltese ten-year bond yields tend to be broadly insulated from event specific volatility in other countries' yields. Simple 'benchmark' regressions are estimated over the period 2007 – 2016, allowing the comparison of actual ten-year bond yields with composite equation outputs. The benchmarked yields based on euro area bonds track consistently actual MGS yields, while from mid-2015 onwards, MGS yields follow closely a benchmark derived on the basis of underlying economic fundamentals.
Keywords: E43; E44; E63; 330